Papillary intralymphatic angioendothelioma: Dabska tumor, - Thadeu Santos Silva; Luciana Rebouças de Araujo; Geise Rezende Paiva; Rodrigo Guimarães Andrade (Sociedade Brasileira de Dermatologia, 2020)
Abstract Papillary intralymphatic angioendothelioma (Dabska tumor) is a rarely metastasizing lymphatic vascular neoplasm that usually affects children and young adults. The majority of these cases occur in soft tissues of extremities, and to date less than 40 cases have been described. Despite the generally indolent evolution, can be locally invasive with the potential to metastasize. We describe a case of a young woman presenting with a plantar lesion, for 9 months and histological diagnosis of Dabska tumor. This neoplasm should be considered in the differential diagnosis of vascular dermatoses, allowing early diagnosis and treatment. Long-term follow-up should be performed.